2022
DOI: 10.1111/jfpp.16858
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and encapsulation of phenolic compounds from the tea of maize husk using maltodextrin and different drying techniques

Abstract: By-products and wastes are produced in food factories and domestic households every day. Most of them are rich sources of bioactive compounds, leading to increasing attention of researchers and companies for the extraction, investigation, and their application in the food formulation (Galanakis, 2021). According to FAO, maize (Zea mays) is one of the most important crops grown worldwide, with a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Balanč et al [ 34 ] encapsulated Carqueja extract by the ionic gelation method using SA and obtained an EE of 49%, while the EE was 73.8% when inulin was added as an additional coating. Navarro-Flores et al [ 35 ] encapsulated phenolic compounds from the leaves of Crotalaria longirostrata using the spray drying method and obtained an EE of 92% using soy protein with maltodextrin, while Pashazadeh et al [ 36 ] used only maltodextrin for the encapsulation of phenolic compounds from corn husks and obtained an EE of 88.29%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Balanč et al [ 34 ] encapsulated Carqueja extract by the ionic gelation method using SA and obtained an EE of 49%, while the EE was 73.8% when inulin was added as an additional coating. Navarro-Flores et al [ 35 ] encapsulated phenolic compounds from the leaves of Crotalaria longirostrata using the spray drying method and obtained an EE of 92% using soy protein with maltodextrin, while Pashazadeh et al [ 36 ] used only maltodextrin for the encapsulation of phenolic compounds from corn husks and obtained an EE of 88.29%.…”
Section: Resultsmentioning
confidence: 99%
“…Higher EE was obtained by SA-GEL (52.63%) an (56.25%), and they were not statistically significantly different from each other obtained are comparable to many studies in the literature that have shown th several different coatings can result in the higher EE of an active ingredient. [34] encapsulated Carqueja extract by the ionic gelation method using SA a an EE of 49%, while the EE was 73.8% when inulin was added as an additio Navarro-Flores et al [35] encapsulated phenolic compounds from the leaves longirostrata using the spray drying method and obtained an EE of 92% using with maltodextrin, while Pashazadeh et al [36] used only maltodextrin for th tion of phenolic compounds from corn husks and obtained an EE of 88.29%.…”
Section: Encapsulation Efficiency Of Grape Pomace Extractmentioning
confidence: 99%